Copper smelter slag leaching with hydrochloric acid in isopropyl alcohol: kinetic study - Nadirov, R. K.; Turan, M. D.; Karamyrzayev, G. A. (Al-Farabi Kazakh Natl Univ, 2020)
The solvometallurgical approach was applied for the first time for processing copper smelter slag. A comparative analysis of the processes of slag leaching with hydrochloric acid dissolved in water, as well as in isopropanol is presented. The use of isopropanol as a solvent leads to an increase in the extraction of copper in comparison with an aqueous solution (84 and 66%, respectively, at 348 K). The rate constants of leaching processes in an alcohol environment are an order of magnitude higher than those in aqueous solutions at 298, 328 and 348 K. The calculated activation energy values were 28.1 +/- 0.8 and 15.7 +/- 0.5 kJ/mol for aqueous and alcohol environments, respectively. Diffusion and chemical reactions are the limiting stages of the leaching in aqueous solution while the only diffusion limits the leaching rate in alcohol environment, according to the shrinking core model. The much higher leaching ability of the isopropanol solution is explained by the lower energy of acid solvation in alcohol in comparison with the energy of hydration in an aqueous solution.
Keywords: copper smelter slag; copper dissolution; leaching; solvometallurgy